Freshwater nematode of Unimas lake and Nanga Merit rivers, Kapit Sarawak - Fatimah A'tirah, Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2010)
The main purpose of this project is to determine the community structure of freshwater nematodes in two distinct ecosystems which are between lotic and lentic ecosystems. These two ecosystems are located in the main lake of UNIMAS and Nanga Merit Rivers, Kapit, Sarawak. Qualitative and quantitative sampling methods were used in conducting this study. Physico-chemical parameters of water were measured and a core of sediment was taken in all stations for particle size analysis. A total of 21 individuals comprising of 9 species were obtained from Nanga Merit Rivers while zero individual in Unimas Lake. Composition of particle size, dissolved oxygen and orthophosphate concentration were influenced nematodes density and distribution based on statistical analysis.